The Perspectives of Nurses and HIV-Positive Women on a Selected Model of Pregnancy Decision-Making Processes in Northeast Thailand - Kownaklai, ๋Jaruwan; Hayter, Mark (Fakultas Ilmu-ilmu Kesehatan, 2022)
Many women living with HIV intend to become pregnant. This is especially true for women who have received ARV treatment for a certain period. The purpose of this study was to explore the perspectives of nurses and Thai pregnant women living with HIV on pregnancy decision-making processes. This is a descriptive and qualitative study. Small group discussions were conducted with five nurses working with HIV-positive women and in-depth interviews were conducted with five Thai HIV-positive pregnant women. A model of the pregnancy decision-making process was provided to participants for the discussion. The nurses’ and women's perspectives on the model can be divided into two themes: 1) The perspective of the selected model and its five sub-themes, namely: 1.1) How the substantive model reflects the pregnancy decision-making process; 1.2) Complexity; 1.3) Usability; 1.4) Strength; 1.5) Weaknesses, in addition to the perspectives of women and nurses on the application of the model. The model reflects the real-life experiences and decision-making processes of Thai women with HIV, where each category shows the trail of the women's decision-making process. However, the model is complex and requires substantial explanation. From the participant's point of view, the model reflects the barriers to the practices and services provided.